Joint Injury and Rehabilitation in Taekwondo-Short Review (International Journal of Innovative Research in Computer Science & Technology, 2023)
Taekwondo is a traditional Korean martial  art combining foot (tae) and hand (kwon) techniques. It is  among the most popular martial arts worldwide and became  an official Olympic discipline in 2012. Taekwondo can be  divided into two types kyorugi and poomsae, kyorugi is  full-contact sport, such as The Olympic Taekwondo, and the  other is non-contact sport, which mainly focuses on  performances and demonstrations, the non-contact sport  known as “Poomsae”. In order to achieve results in various  competitions, the training of ordinary athletes focuses on  sparring (Olympic style) taekwondo. In recent years,  however, many experienced athletes have begun to engage in  mind training centered on the unity of posture (Poosae).  Poosae is the only non-contact training in taekwondo.  Poomsae consists of 13 defined patterns of movement, which  are repeated over and over in practice.
Keywords: Taekwondo; Injury; Rehabilitation